DEATH CAUSES AND THEIR PREDICTION IN PATIENTS WITH THE ST SEGMENT ELEVATION ACUTE CORONARY SYNDROME AND PRE-HOSPITAL THROMBOLYSIS - S. N. Morozov; A. I. Fedorov; K. S. Loskutova; A. L. Vertkin (Кардиоваскулярная терапия и профилактика)
Aim. To assess effectiveness and safety of pre-hospital medical treatment in patients with acute coronary syndrome and ST segment elevation (ST-ACS) who are undergoing thrombolytic therapy (TLT); to identify TLT complications and the methods for their prediction.Material and methods. In total, the pre-hospital TLT effectiveness was assessed in 237 patients. The comparison group included 274 patients who did not undergo TLT, due to various reasons. The causes of death by Day 7–10 were analysed.Results. The leading cause of death was cardiogenic shock. In addition, in the main group, indirect myocardial rupture was a cause of death more often than in the comparison group (28% vs. 5,3%). Indirect myocardial rupture was associated with haemorrhagic complications of pre-hospital TLT. The proposed method for predicting TLT complications is based on the TIMI scale: 1–4 points suggest TLT safety; 4–5 points correspond to a higher risk of external myocardial rupture (11,6%), which implies the need to perform TLT under control of blood coagulation parameters; and ≥6 points denote the need to avoid pre-hospital TLT and use a mechanic reperfusion strategy.Conclusion. Among ST-ACS patients, mortality levels were 20,9%, which was 2,4 times higher than in the comparison group. In the main group, the morphological data obtained at autopsy demonstrated hemorrhagic myocardial transformation, which was associated with the high risk of indirect myocardial rupture (28,1%). In patients with pre-existing arterial hypertension and with the time from the ST-ACS onset of 2–3 hours, the risk of indirect myocardial rupture should be predicted, based on the TIMI scale. This will facilitate more effective assessment of the systemic TLT complication risk and selection of the optimal reperfusion strategy.